Faire ou non confiance aux gestionnaires du risque ? - Hervé Flanquart; Anne-Peggy Hellequin; Pascal Vallet (Territoire en Mouvement)
The confidence or trust that the people and institutions responsible for managing territorial risk inspire in the individuals subjected to this risk is an important factor in the analysis of territorial vulnerability because low confidence levels, or near total lack of confidence, can exacerbate risks, be they natural or technological. A team of sociologists and geographers conducted an inquiry by questionnaire and observation in a village in the north of France—situated in an industrial-portuary zone and thus surrounded by "Seveso" industrial sites—in order to measure the level of confidence that people have in a variety of risk managers, including local authorities, fire and rescue personnel, police and industry. The village inhabitants, mostly middle and working class and living in large family groups, appear to be most confident of those mangers who are in close geographical proximity and who are perceived to be competent and disinterested. Thus, personnel from the fire, rescue, & police departments and the town hall are high on the list of those that inspire confidence, while the European governmental bodies are at the bottom. In addition, although socio-demographic characteristics—gender, age, level of education, or socio-professional category—are often cited in sociological literature as highly discriminating variables for risk perceptions and risk management, these characteristics didn't seem to have much influence in this study. In fact, in the case of this village subjected to technological risk, it would be more pertinent to build a typology disconnected from these variables, a typology consisting of those who have "general confidence" in all categories of risk managers, those that find only "politicians" reliable, those that have confidence only in the "specialists" (who are more numerous among the most